A CULTURALLY – ADAPTED MENTAL HEALTH ASSESMENT FORMAT (BASAHARI) FOR NURSING EDUCATION : A RESEARCH AND DEVELOPMENT STUDY - Dias, Maria Frani Ayu Andari; Lanawati, Lanawati; Raya, Mardha; Villanueva-Tamse, Maria Rita Rita (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2026)
Introduction: Comprehensive and culturally sensitive mental health assessment remains a challenge in Indonesian nursing education, where existing formats are often too generic for specific local contexts like the Banjar culture. This study aimed to develop and test the effectiveness of the BASAHARI assessment format, which integrates clinical standards with local Banjar cultural wisdom, to improve the assessment skills of nursing students.Method: This study employed a Research and Development (R&D) design at a private nursing college and a provincial psychiatric hospital in Indonesia. The initial needs analysis involved in-depth interviews with seven senior psychiatric nurses to identify practice needs and challenges. Based on these findings, the BASAHARI format was developed. Its effectiveness was subsequently evaluated using a quasi-experimental, pre-test/post-test design with a cohort of 40 nursing students. Data were analyzed using a Paired Samples T-Test.Results: The implementation of the BASAHARI format led to a statistically significant improvement in students' skills across all measured domains (p < 0.001). The mean cognitive score increased by 10.20 points (t=13.924), the mean psychomotor score increased by 9.87 points (t=11.968), and the mean attitude score increased by 11.55 points (t=12.551).Conclusion: The BASAHARI assessment format is an effective tool for significantly improving the cognitive, psychomotor, and attitude domains of nursing students' mental health assessment capabilities. Its integration into nursing curricula and clinical practice is recommended to foster culturally competent care.